The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/sltb.12432
|View full text |Cite
|
Sign up to set email alerts
|

Current and Military‐Specific Gender Minority Stress Factors and Their Relationship with Suicide Ideation in Transgender Veterans

Abstract: Research suggests the prevalence of suicide ideation and suicide attempts in the transgender veteran community may be upwards of 20 times higher than nontransgender veterans, who are known to be at increased risk than the general US population. This study aimed to understand the potential influence of external and internal minority stress experienced during and after military service on past-year and recent suicide ideation in a sample of 201 transgender veterans. Nonparametric bootstrapping analyses indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 37 publications
1
37
0
2
Order By: Relevance
“…Finally, a fourth study applying the PMF to 201 transgender veterans explored the influence of distal and proximal minority stressors experienced during and after military service on suicide ideation [ 33 ]. Authors found that distal stressors (i.e., past-year anti-transgender discrimination and rejection) indirectly predicted suicide ideation through feelings of shame related to gender identity (i.e., proximal stressor).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a fourth study applying the PMF to 201 transgender veterans explored the influence of distal and proximal minority stressors experienced during and after military service on suicide ideation [ 33 ]. Authors found that distal stressors (i.e., past-year anti-transgender discrimination and rejection) indirectly predicted suicide ideation through feelings of shame related to gender identity (i.e., proximal stressor).…”
Section: Introductionmentioning
confidence: 99%
“…Summarizing, actual scientific literature reports evidence that both group-specific processes [ 5 , 31 , 33 ] and general psychological processes [ 32 ] mediate the relationship between external stressors and negative mental health outcomes, and that group-level coping mechanisms [ 5 ] buffer the effect of stressors on mental health. Notwithstanding that, no previous studies took into account the internal differentiation of internalized transphobia while analyzing its vertical and horizontal nature.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that there are >150,000 transgender active duty service members, Veterans, and reservists (Ahuja et al, 2019). Although the future of transgender military policy remains to be seen, it is critical to understand that individuals who identify as transgender will continue to serve in the military, but some may conceal their gender identity during their time in the service due to fear of discrimination (Tucker et al, 2019). Nonetheless, transgender individuals will seek care at the VHA following their time in the military and should be supported in achieving optimum health outcomes.…”
Section: Gender Dysphoria In United States Veterans and Military Persmentioning
confidence: 99%
“…Sociocultural factors, including social support (or lack thereof) and access to gender affi rmation care appear to infl uence trajectories among Veterans with gender dysphoria, with high levels of experienced discrimination associated with increases in suicidal ideation in this population (Carter et al, 2019;Tucker et al, 2019). Discrimination can be defi ned as "unfair treatment by outgroup members [i.e.…”
mentioning
confidence: 99%
“…Furthermore, almost all participants recruited for this study indicated a binary gender identity. This is particularly salient as military policy requires service members (those who are allowed to continue serving) to comply with either male or female regulations and standards (DoD, 2016; (Tucker et al, 2018) and recommended efforts to reduce transgender veterans' exposure to minority stressors during and after service as a prevention strategy. Recent studies have also identified social support and connection as an important strategy for increasing resilience among transgender veterans (Carter et al, 2019).…”
Section: Strengths and Limitationsmentioning
confidence: 99%